Non-invasive brain stimulation associated mirror therapy for upper-limb rehabilitation after stroke: Systematic review and meta-analysis of randomized clinical trials - Zhao, Qingqing; Li, Hong; Liu, Yu; Mei, Haonan; Guo, Liying; Liu, Xianying; Tao, Xiaolin; Ma, Jiang (Frontiers in Neurology, 2022)
Background: Noninvasive brain stimulation (NIBS) techniques and mirror therapy (MT) are promising rehabilitation measures for stroke. While the combination of MT and NIBS has been employed for post-stroke upper limb motor functional rehabilitation, its effectiveness has not been examined. Objective: This study aimed to evaluate the effectiveness of combined MT and NIBS in the recovery of upper limb motor function in stroke patients. Methods: The search was carried out in PubMed, EMBASE, Cochrane Library, Web of Science, Science Direct, CNKI, WANFANG and VIP until December 2021. Randomized clinical trials (RCTs) comparing MT or NIBS alone with the combination of NIBS and MT in improving upper extremity motor recovery after stroke were selected. A meta-analysis was performed to calculate the mean differences (MD) or the standard mean differences (SMD) and 95% confidence intervals (CI) with random-effect models. Subgroup analyses were also conducted according to the types of control group, the types of NIBS, stimulation timing and phase poststroke. Results: A total of 12 articles, including 17 studies with 628 patients, were reviewed in the meta-analysis. In comparison with MT or NIBS alone, the combined group significantly improved body structure and function (MD=5.97; 95% CI: 5.01-6.93; P < 0.05), activity levels (SMD=0.82; 95% CI 0.61-1.02; P < 0.05). For cortical excitability, the motor evoked potential cortical latency (SMD=-1.05; 95% CI: -1.57- -0.52; P < 0.05) and the central motor conduction time (SMD=-1.31 95% CI: -2.02- -0.61; P < 0.05) of the combined group were significantly shortened. A nonsignificant homogeneous summary effect size was found for MEP amplitude (SMD = 0.47; 95%CI = -0.29 to 1.23; P = 0.23). Subgroup analysis showed that there is an interaction between the stimulation sequence and the combined treatment effect. Conclusion: In this meta-analysis of randomized clinical trials, in comparison to the control groups, MT combined with NIBS promoted the recovery of upper extremity motor function after stroke, which was reflected in the analysis of body structure and function, activity levels, and cortical excitability.